3D Bioprinting Allows the Establishment of Long-Term 3D Culture Model for Chronic Lymphocytic Leukemia Cells - Sbrana, Francesca Vittoria; Pinos, Riccardo; Barbaglio, Federica; Ribezzi, Davide; Scagnoli, Fiorella; Scarfò, Lydia; Redwan, Itedale Namro; Martinez, Hector; Farè, Silvia; Ghia, Paolo; Scielzo, Cristina (Frontiers in Immunology, 2021)
Chronic Lymphocytic Leukemia (CLL) represents the most common leukemia in the western world and remains incurable. Leukemic cells organize and interact in the lymphoid tissues, however what actually occurs in these sites has not been fully elucidated yet. Studying primary CLL cells in vitro is very challenging due to their short survival in culture and also to the fact that traditional two-dimensional in vitro models lack cellular and spatial complexity present in vivo. Based on these considerations, we exploited for the first time three-dimensional (3D) bioprinting to advance in vitro models for CLL. This technology allowed us to print CLL cells (both primary cells and cell lines) mixed with the appropriate, deeply characterized, hydrogel to generate a scaffold containing the cells, thus avoiding the direct cell seeding onto a precast 3D scaffold and paving the way to more complex models. Using this system, we were able to efficiently 3D bioprint leukemic cells and improve their viability in vitro that could be maintained up to 28 days. We monitored over time CLL cells viability, phenotype and gene expression, thus establishing a reproducible long-term 3D culture model for leukemia. Through RNA sequencing (RNAseq) analysis, we observed a consistent difference in gene expression profile between 2D and 3D samples, indicating a different behavior of the cells in the two different culture settings. In particular, we identified pathways upregulated in 3D, at both day 7 and 14, associated with immunoglobulins production, pro-inflammatory molecules expression, activation of cytokines/chemokines and cell-cell adhesion pathways, paralleled by a decreased production of proteins involved in DNA replication and cell division, suggesting a strong adaptation of the cells in the 3D culture. Thanks to this innovative approach, we developed a new tool that may help to better mimic the physiological 3D in vivo settings of leukemic cells as well as of immune cells in broader terms. This will allow for a more reliable study of the molecular and cellular interactions occurring in normal and neoplastic conditions in vivo, and could also be exploited for clinical purposes to test individual responses to different drugs.